2021
DOI: 10.3390/su132111890
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspective on Remote On-Line Teaching and Learning at the University of Latvia in the First and Second COVID-19 Period

Abstract: In Spring 2020, due to the rapid spread of COVID-19, all educational institutions in Latvia, including the University of Latvia (UL), transitioned from face-to-face on-site learning to remote learning. After a short period of face-to-face on-site learning in autumn, UL returned to remote learning in November for the second time. This paper investigates the UL students’ perspectives on remote teaching and learning at the UL during the first and second COVID-19 periods. The research assesses several remote study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, as indicated above, such pedagogical transformation is not easy for teachers who have been practicing traditional teaching methods. Therefore, they need proper training to improve their pedagogical knowledge and ICT skills and competencies [26,27]. This could help them manage online learning effectively and, thus, address students' learning needs using student-centered pedagogy.…”
Section: Teaching and Learning During The Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as indicated above, such pedagogical transformation is not easy for teachers who have been practicing traditional teaching methods. Therefore, they need proper training to improve their pedagogical knowledge and ICT skills and competencies [26,27]. This could help them manage online learning effectively and, thus, address students' learning needs using student-centered pedagogy.…”
Section: Teaching and Learning During The Covid-19mentioning
confidence: 99%
“…There are several research projects conducted worldwide regarding online teaching and learning, particularly after the outbreak of the COVID-19 pandemic [6,8,26,[28][29][30][31][32][33][34][35][36]. However, most of these research papers are based on quantitative studies, particularly on survey of students.…”
Section: Teaching and Learning During The Covid-19mentioning
confidence: 99%
“…The objective is to evaluate the sustainability of the methodology suggested by previous experiments in an early meta-COVID-19 period or in future blended learning environments. To do so, the evaluation methods used exactly the same tools and in particular the same communication platform, while taking into account the changing guidelines imposed by the health situation [38].…”
Section: Data Sourcesmentioning
confidence: 99%
“…For example, ERT implementation at the School of Telecommunication Engineering at the University of Spain, the research by Iglesias-Pradas et al reported that students' academic performance was well kept [13]. In the case of a university in Latvia, it was reported that students and faculties were well adapted to online courses, which can be classified as ERT, and see the new prospects as new ways of teaching in the long run [14]. Şenda ǧ and Odabaşi discuss that there are no particular differences in learning outcomes between online and face-to-face teaching [15].…”
Section: Introductionmentioning
confidence: 99%